The Performance Of English Speaking Skill Used By The Receptionist of Purna Wisata Tour And Travel - Sitti Halijah; Dewi Bastian (Tamaddun Life, 2018)
The reseach objectives are to know whats ymbols are performed in Lariangi dance and what meaning are conveyed in the symbols performed in Lariangi dance. The research used descriptive qualitative method to take information. The writer obsereved the house in Liya village and took some informations from them and interviewed and documented by using recorded and camera. This research also took the datum from some books, articles, internet which associat with the symbols in Lariangi dance in Wakatobi Southeast Sulawesi. The research resulted in the part of symbols in Lariangi dance start from dress, accessories, movement of the dance and the songs of Lariangi dance. The result of the research was consisted in four part. First, the symbols found in dress there are six namely Kombo Monihi, Kombo Meha, Punto/Wuray Nibelo Biru, Laka/Wuray Meha, Kambero, and Lenso/Saputangan symbolyzes sweat rag of King Buton. The second, there are eight symbols and their meaning found in accessories, namely Panto and Pintoru, Hepupu/Konde, Kamba Konde, Toboy Kamba, Hebindu/Sangi-Sangi, Kalo, Naga, Sekori Keponto Posusu symbolyzes degrees nobility. The third, there are four symbols found in movement of Lariangi dance namely, Hematu kepooli le..le, Pajogi/Nyibing/Ngifi, Nabu/Tau, and Lariangi symbolyzes Lighting. The last is symbols found in song of Lariangi dance there are nine songs namely Mangu-Mangu, Ole-Ole, Doumaraia, Denda Aule, Sailila, Waindi-Indi, Rongande, Jojongana, and Salatu symbolyzes as thankful to Allah SWT.